Decks and Treatments of A Documentary - Sze Min, Bong; Nur Shahrina Umira, Idris; Pei Pei, Leong; Chong Lee, Yow (Mini Film Festival, 2022)
Infographics on decks and treatments of a documentary. The content is extracted from MFF Doc Workshop (1) presented by Ms. Cheyenne Tan, designed by Sze Min, Shahrina, PeiPei, advised and edited by Yow.